Density functional theory (DFT), molecular docking, and xanthine oxidase inhibitory studies of dinaphthodiospyrol S from Diospyros kaki L - Tareq Abu-Izneid; Abdur Rauf; Zubair Ahmad; Abdul Wadood; Khurshid Ayub; Naveed Muhammad; Yahya S. Al-Awthan; Maria Maqbool; Omar S. Bahattab; Hassan A. Hemeg; Saima Naz; Dorota Formanowicz (Elsevier, 2024)
In this work, we investigated Diospyros kaki extract and an isolated compound for their potential as xanthine oxidase (XO) inhibitors, a target enzyme involved in inflammatory disorders. The prepared extract was subjected to column chromatography, and dinaphthodiospyrol S was isolated. Then XO inhibitory properties were assessed using a spectrophotometry microplate reader. DMSO was taken as a negative control, and allopurinol was used as a standard drug. The molecular docking study of the isolated compound to the XO active site was performed, followed by visualization and protein-ligand interaction. The defatted chloroform extract showed the highest inhibitory effect, followed by the chloroform extract and the isolated compound. The isolated compound exhibited significant inhibitory activity against XO with an IC50 value of 1.09 µM. Molecular docking studies showed that the compound strongly interacts with XO, forming hydrogen bond interactions with Arg149 and Cys113 and H-pi interactions with Cys116 and Leu147. The binding score of −7.678 kcal/mol further supported the potential of the isolated compound as an XO inhibitor. The quantum chemical procedures were used to study the electronic behavior of dinaphthodiospyrol S isolated from D. kaki. Frontier molecular orbital (FMO) analysis was performed to understand the distribution of electronic density, highest occupied molecular orbital HOMO, lowest unoccupied molecular orbital LUMO, and energy gaps. The values of HOMO, LUMO, and energy gap were found to be −6.39, −3.51 and 2.88 eV respectively. The FMO results indicated the intramolecular charge transfer. Moreover, reactivity descriptors were also determined to confirm the stability of the compound. The molecular electrostatic potential (MEP) investigation was done to analyze the electrophilic and nucleophilic sites within a molecule. The oxygen atoms in the compound exhibited negative potential, indicating that they are favorable sites for electrophilic attacks. The results indicate its potential as a therapeutic agent for related disorders. Further studies are needed to investigate this compound's in vivo efficacy and safety as a potential drug candidate.